Gadd45 in stress signaling - Liebermann, Dan A (BioMed Central, 2008)
Gadd45 genes have been implicated in stress signaling in response to physiological or environmental stressors, which results in cell cycle arrest, DNA repair, cell survival and senescence, or apoptosis. Evidence accumulated implies that Gadd45 proteins function as stress sensors is mediated by a complex interplay of physical interactions with other cellular proteins that are implicated in cell cycle regulation and the response of cells to stress. These include PCNA, p21, cdc2/cyclinB1, and the p38 and JNK stress response kinases. What deterministic factors dictate whether Gadd45 and partner proteins function in either cell survival or apoptosis remains to be determined. An attractive working model to consider is that the extent of cellular/DNA damage, in a given cell type, dictates the association of different Gadd45 proteins with particular partner proteins, which determines the outcome.